O efeito neuroprotetor da Espermina em condições de inflamação ocorre via BDNF, ativação do receptor TrkB, CREB e alteração na neurogênese - Perez, Pâmella Karina Santana Frühauf (2019)
Lipopolysaccharide (LPS) has been long known to promote neuroinflammation and disrupting memory pathway and neurogenesis. Since spermine, one of the main natural polyamines in the central nervous system, protects from LPS induced memory deficit by a mechanism that comprises GluN2B receptors, the aim of the present study was to determine whether brain-derived neurotrophic factor (BDNF), tropomyosin-related kinase B (TrkB) receptor and cAMP response element binding (CREB), are involved in this protective effect of spermine. Furthermore, we also investigated the effect of spermine on neuroinflammation conditions on proliferation and differentiation of neural stem cells (NSCs) and BDNF levels in vitro. Adult male Swiss albino mice received, immediately after training in the novel object recognition task, saline or LPS (250 μg/kg, i.p.); 5 min later they received saline or spermine (0.3 mg/kg, i.p.) and, when specified, 5 min thereafter saline or the TrkB receptor antagonist ANA-12 (0.5 mg/kg, i.p.) in different flanks. Animals were tested 24 h after training. Spermine protected from LPS-induced memory deficit and this protective effect was reversed by ANA-12. In a subset of animals BDNF, CREB and phospho-CREB immunoreactivity was determined in the hippocampi and cerebral cortex 4 h after spermine injection. For in vitro studies, NPCs were treated with LPS (100 nM) and / or spermine (1-100 nM) for analysis of cellular migration (24 h of neural differentiation) neuritogenesis (3 days of neural differentiation), as well as, neurogenesis, gliogenesis and BDNF levels (7 days of neural differentiation). ANA-12 reversed the protective effect of spermine on LPS-induced memory deficit. Spermine reversed the decrease of mature BDNF levels induced by LPS in both hippocampus and cerebral cortex. Moreover, spermine increased the phospho-CREB and phospho-CREB/total-CREB ratio expression in cerebral cortex of LPS-treated mice. In addition, in vitro experiments demonstrated that spermine increased cell migration and the number and length of neurites and prevented LPS-induced impairment of neuritogenesis. Moreover, spermine prevented LPS-induced decrease of neuronal differentiation of NSCs and prevented LPS-induced gliogenesis. Spermine also reversed the decrease of BDNF levels induced by neuroinflammation in NSCs. Collectively, the results support that the protective effect of spermine on LPS-induced memory deficits depends on TrkB receptor activation and is accompanied by restoration of mature BDNF levels in hippocampus and cerebral cortex, as well as increased CREB phosphorylation in the cerebral cortex. Moreover, spermine may restore the balance between neurogenesis and gliogenesis possibly by recovering BDNF levels in an inflammatory process, which represents a new perspective for neuro-restoration.